PERTUMBUHAN ROHANI ANAK DALAM KELUARGA KRISTEN MENURUT EFESUS 6:4 - Bryan Roy; Antonius Yosef (STT Bethel The Way, 2019)
This study aims to examine the spiritual growth of children in Christian families according to the biblical perspective. The method used is the exegesis method by studying the background and paying attention from the point of view of the principle of biblical interpretation in general. The qualitative word itself implies an emphasis on processes and meanings that are not strictly examined or measured in terms of quantity, intensity, and frequency, but emphasize the nature ofsocially constructed reality, the relationship between the researcher and the investigated, and the situational limitations that make up research. The results of this study tend to highlight the main issue, namely: The existence of a Bible command about educating children that is not taken seriously by Christian parents. The spiritual growth of children in a Christian family is an important moment for the family. Moral damage to children in the present can damage future generations. The church must be involved in changing the wrong culture. Teaching in the family, verbally and non-verbally will ensure the future generations to worship God. Increasing the quality of the role of parents in children's spiritual growth activities in Christian families is very emphasized.